LEGAL OPINION AHLI SYARIAH PASAR MODAL (ASPM) DALAM INDUSTRI PASAR MODAL SYARIAH DI INDONESIA - indra rahmatullah (Universitas Muhammadiyah Surakarta, 2018)
To ensure that the sharia capital market keeps value of sharia, legal opinion from Sharia Capital Market Expert (ASPM) is required. ASPM provides legal opinion (sharia) for parties planning to conduct transaction in sharia capital market with 2 (two) stages: filtering from financial aspect and business screening. In financial screening, ASPM will ensure financial company is free from usury while business screening, ASPM will assess the business company activity is not against the sharia. ASPM task is almost same with other supporting professions namely Legal Consultant in the Capital Market (Conventional) which provides legal opinion when there are parties conducting transaction in the capital market. But ASPM has differentiation because legal opinion (sharia) made it must consider the Islamic law (sharia).